An epidemiological study of unintentional pediatric firearm fatalities in the USA, 2009-2018 - Arti Vaishnav; Gary A. Smith; Jaahnavi Badeti; Nichole L. Michaels (BMC, 2023)
Abstract Background Firearm injuries are the leading cause of mortality among children and adolescents 1-19 years old in the USA. Many prior studies on this topic lack detailed information about the circumstances of the firearm fatalities and include decedents and shooters of all ages. This study characterizes firearm fatalities in the USA in which children < 15 years old unintentionally killed themselves or another child. Methods Ten years of data from the National Violent Death Reporting System were analyzed. Unintentional firearm fatalities among children were reviewed to identify characteristics of decedents and the children who inflicted the deaths, their relationship, and circumstances of the deaths. There were 279 firearm fatalities during the study period involving children < 15 years old who unintentionally killed themselves or another child < 15 years old. Results Most victims were male (81.4%), and 40.9% were 2-4 years old. Most incidents (64.0%) occurred at the victim's residence, and in 80.9% of cases the firearm owner was a relative of the shooter. In the < 5-year age group, 80.3% of injuries were self-inflicted, and in the 10-14-year age group, 32.3% of shooters were a friend of the victim. Conclusion This study highlights that children in the USA are shooting themselves and each other in their own homes, and often accessing firearms owned by family members. These findings can be used to guide prevention efforts, such as child access prevention laws, to reduce the number of pediatric firearm fatalities in the future.